2018
DOI: 10.1111/ecog.03632
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of the spatial scale that best predict primate responses to landscape structure

Abstract: Understanding the effect of landscape structure on biodiversity is critically needed to improve management strategies. To accurately evaluate such effect, landscape metrics need to be assessed at the correct scale, i.e. considering the spatial extent at which species–landscape relationship is strongest (scale of effect, SE). Although SE is highly variable, its drivers are poorly known, but of key relevance to understand the way species use the landscape. In this study, we evaluate whether and how species trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 50 publications
7
49
0
4
Order By: Relevance
“…We found two general scales of effect in this study (~1.0–2.3 km 2 and > 23 km 2 ) that may be used as a starting point for researchers interested in evaluating the impact of landscape structure on medium‐sized arboreal mammals. In fact, the smaller scale of effect is within the range of scales reported in previous studies (1.0 km 2 : Arroyo‐Rodríguez, González‐Perez, et al, ; 1.26 km 2 : Ordóñez‐Gómez et al, ; 0.98–1.58 km 2 : Galán‐Acedo et al, ). However, in half of the cases, we found scales of effect equal to the largest scale (>23 km 2 ).…”
Section: Discussionsupporting
confidence: 81%
“…We found two general scales of effect in this study (~1.0–2.3 km 2 and > 23 km 2 ) that may be used as a starting point for researchers interested in evaluating the impact of landscape structure on medium‐sized arboreal mammals. In fact, the smaller scale of effect is within the range of scales reported in previous studies (1.0 km 2 : Arroyo‐Rodríguez, González‐Perez, et al, ; 1.26 km 2 : Ordóñez‐Gómez et al, ; 0.98–1.58 km 2 : Galán‐Acedo et al, ). However, in half of the cases, we found scales of effect equal to the largest scale (>23 km 2 ).…”
Section: Discussionsupporting
confidence: 81%
“…3), indicating these scales were not merely reflective of urban heterogeneity but rather were species-specific responses to the urban landscape (De Knegt et al 2011). These results mirror recent studies that have found a general lack of support for theoretical predictions regarding scale of effect across several taxa (Galán-Acedo et al 2018, Martin 2018, Gestich et al 2019, Moraga et al 2019, although other work has suggested that body size correlates with scale of effect in birds (Thornton and Fletcher 2014). 4, Supplementary material Appendix 4).…”
Section: Discussionsupporting
confidence: 73%
“…90%; scale 90 ). This disparity implies that the traditional focus on scale max in evaluations of scales of effect (Holland et al 2004, Galán-Acedo et al 2018, Gestich et al 2019 has likely resulted in an overall underestimation of the scale of landscape effects on wildlife (Miguet et al 2017). Miguet et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…3). This is alarming, as an increasing number of studies demonstrate that if landscape variables are not measured at the optimal scale, species responses to landscape predictors can be poorly estimated or missed altogether, potentially leading to erroneous conclusions about the effects of landscape structure on species (Holland, Fahrig & Cappuccino, 2005;de Knegt et al, 2010;Jackson & Fahrig, 2012;Miguet et al, 2016;Galán-Acedo et al, 2018;Gestich et al, 2019).…”
Section: (2) Potential Methodological Caveatsmentioning
confidence: 99%
“…landscape size) within which landscape variables are measured (Jackson & Fahrig, ; Miguet et al, ; Martin, ), and this has specifically been shown in primate research (e.g. Ordóñez‐Gómez et al, ; Galán‐Acedo et al, ). Significant species–landscape relationships may be undetected (i.e.…”
Section: Introductionmentioning
confidence: 99%